ISSUES OF IMPLEMENTATION OF THE RIGHTS OF PERSONS WITH LIMITED FREEDOM TO RECEIVE HIGHER EDUCATION - Bokiev Jakhongir (Scholar Express Journals, 2023)
There are many significant issues that need to be resolved in the domain of the achievement of human rights in today's fast developing globe. Particularly, criminality of all kinds is rising in newly developing partnerships. The preservation of the rights of those incarcerated has traditionally received special consideration. The dilemma of implementing the right to higher education for those serving prison terms for crimes connected to the restriction of personal freedom is analyzed scientifically in this article. The benefits of foreign practice in this area are examined, and the prospect of incorporating them into national law is considered
Keywords: expulsion from the student; the right to higher education; punishments; deprivation of liberty